2016
DOI: 10.1371/journal.pone.0166775
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket Spending on Out-Patient Care in India: Assessment and Options Based on Results from a District Level Survey

Abstract: Out-of-pocket spending at out-patient departments (OPD) by households is relatively less analyzed compared to hospitalization expenses in India. This paper provides new evidence on the levels and drivers of expenditure on out-patient care, as well as choice of providers, using household survey data from 8 districts in 3 states of India. Results indicate that the economically vulnerable spend more on OPD as a proportion of per capita consumption expenditure, out-patient care remains overwhelmingly private and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 16 publications
4
45
0
Order By: Relevance
“…Studies reported that the poor were more likely to be deterred by the perceived high prices. 32 , 33 This is particularly worrisome as the burden of noncommunicable diseases, which are associated with higher out-of-pocket expenditure and catastrophic health expenditure 22 , 34 , is increasing fast in the Region.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that the poor were more likely to be deterred by the perceived high prices. 32 , 33 This is particularly worrisome as the burden of noncommunicable diseases, which are associated with higher out-of-pocket expenditure and catastrophic health expenditure 22 , 34 , is increasing fast in the Region.…”
Section: Discussionmentioning
confidence: 99%
“…We opine that improving access to the government healthcare services along with improved quality is much needed to address the healthcare needs of the poor and to reduce the OOPE as expressed by various scholars (Gupta, Reddy, Semwal, & Singh, ; Gupta, Chowdhury, Prinja, & Trivedi, ; Gupta & Muraleedharan, ; Rao, Selvaraju, Nagpal, & Sakthivel, ; Tripathy et al, ). Need for improving access to public sector health services and social protection policies was expressed (Brinda, Rajkumar, Enemark, Rajkumar, Enemark, Prince, & Jacob, ; Daivadanam, Thankappan, Sarma, & Harikrishnan, ; Gupta et al, ; Karan, Selvaraj, & Mahal, ). Babu and Kusuma () opined that both public and private firms who engage a great number of informal workers, mainly the internal migrants, should provide basic amenities including the healthcare as the migrants were usually excluded for accessing services.…”
Section: Discussionmentioning
confidence: 98%
“…Selvaraj and Karan (2012) could not find any beneficial effects of any health insurance on out of pocket healthcare expenditures. We opine that improving access to the government healthcare services along with improved quality is much needed to address the healthcare needs of the poor and to reduce the OOPE as expressed by various scholars (Gupta, Reddy, Semwal, & Singh, 2017;Gupta, Chowdhury, Prinja, & Trivedi, 2016;Gupta & Muraleedharan, 2014;Rao, Selvaraju, Nagpal, & Sakthivel, 2005;Tripathy et al, 2016). Need for improving access to public sector health services and social protection policies was expressed (Brinda, Rajkumar, Enemark, Rajkumar, Enemark, Prince, & Jacob, 2012;Daivadanam, Thankappan, Sarma, & Harikrishnan, 2012;Gupta et al, 2016;Karan, Selvaraj, & Mahal, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In India, evidence suggests that outpatient care is more impoverishing than inpatient care in urban and rural areas alike. A study done in three Indian states showed that 3.5% of the population fell below the poverty line on account of out-of-pocket expenses on healthcare, but this decreased to 0.5% if outpatient care was excluded 28. In Pakistan, 90% of out-of-pocket payment is for outpatient services 29.…”
Section: Challenges Of Primary Care In South Asiamentioning
confidence: 99%